Improving nutrition through biofortification–A systematic review - Ofori, Kelvin F.; Antoniello, Sophia; English, Marcia M.; Aryee, Alberta N. A. (Frontiers in Nutrition, 2022)
Nutritious foods are essential for human health and development. However, malnutrition and hidden hunger continue to be a challenge globally. In most developing countries, access to adequate and nutritious food continues to be a challenge. Although hidden hunger is less prevalent in developed countries compared to developing countries where iron (Fe) and zinc (Zn) deficiencies are common. The United Nations (UN) 2nd Sustainable Development Goal was set to eradicate malnutrition and hidden hunger. Hidden hunger has led to numerous cases of infant and maternal mortalities, and has greatly impacted growth, development, cognitive ability, and physical working capacity. This has influenced several countries to develop interventions that could help combat malnutrition and hidden hunger. Interventions such as dietary diversification and food supplementation are being adopted. However, fortification but mainly biofortification has been projected to be the most sustainable solution to malnutrition and hidden hunger. Plant-based foods (PBFs) form a greater proportion of diets in certain populations, hence, fortification of PBFs is relevant in combating malnutrition and hidden hunger. Agronomic biofortification, plant breeding, and transgenic approaches are some currently used strategies in food crops. Crops such as cereals, legumes, oilseeds, vegetables, and fruits have been biofortified through all these three strategies. The transgenic approach is sustainable, efficient, and rapid, making it suitable for biofortification programs. Omics technology has also been introduced to improve the efficiency of the transgenic approach.